St. Vincent and the Grenadines : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2006)
This paper describes the IMF's projections and estimates of St. Vincent and the Grenadines on prices and wages, GDP by economic activity at current factor cost and by type of expenditure at current prices, petroleum consumption and unit values, consumer price index, summary of central government operations, revenues and grants, expenditure, net lending and investment plan and consolidated public sector operations, national insurance scheme, monetary survey, consolidated balance sheets of foreign commercial banks and commercial banks, interest rate structure of commercial banks, summary of balance payments, public sector external debt, et cetera.